Pengaruh Struktur Modal Dan Kebijakan Dividen Terhadap Nilai Perusahaan Dan Dampaknya Terhadap Harga Saham Pada Sektor Pertambangan Periode 2016-2020 - Widya Warisman; Andi Yudha Amwila (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
The capital market is a facility that is prepared to trade stocks, bonds and various other types of securities. Before buying a stock, investors must conduct an analysis that is expected to affect the stock price. In addition, it must have a benchmark by investing in a company that will get the quality as expected. One of the factors that affect stock prices is the fundamental condition seen from the company's financial condition. This study uses a comparative descriptive method with a quantitative approach. The data used are in the form of company financial statements through document studies. The sampling technique used is purposive sampling with predetermined criteria in order to obtain 10 samples of companies. Data analysis used path analysis with SPSS as the analysis tool. The purpose of the study was to determine the effect of capital structure and dividend policy on firm value and stock prices. The results of this study indicate that the capital structure has no effect on firm value dividend policy has a significant positive effect on firm value. Meanwhile, capital structure has a significant negative effect on stock prices, dividend policy has no effect on stock prices and firm value has a significant positive effect on stock prices. Firm value is not able to mediate capital structure on stock prices while firm value is able to mediate policy on stock price dividends. Keywords : Capital Structure, Dividend Policy, Firm Value, Stock Price.